2004
DOI: 10.3138/cjccj.46.4.423
|View full text |Cite
|
Sign up to set email alerts
|

Safe Streets for Whom? Homeless Youth, Social Exclusion, and Criminal Victimization

Abstract: This article explores the victimization experiences of street youth living in Toronto, Canada. It is argued that street youth are much more likely than domiciled youth to be victims of a broad range of crimes. In particular, young women who are homeless face increased vulnerability to specific forms of violent crime, including sexual assault. The circumstances that produce such high levels of criminal victimization among street youth are myriad and complex. While background variables (a history of violence), l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
187
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 207 publications
(203 citation statements)
references
References 39 publications
10
187
0
6
Order By: Relevance
“…For instance, several provinces and municipalities have enacted laws that have essentially criminalized the income generating activities of this population. The rather ironically titled "Safe Streets Act" of Ontario [18] was enacted purportedly to protect the public, ignoring the fact that people who are homeless are much more likely to be victims of crime [15]. Research has demonstrated that people who engage in such income generating activities do so because they provide 'cash in hand' on a daily basis needed to meet subsistence needs [19].…”
Section: The Canadian Response To Homelessnessmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, several provinces and municipalities have enacted laws that have essentially criminalized the income generating activities of this population. The rather ironically titled "Safe Streets Act" of Ontario [18] was enacted purportedly to protect the public, ignoring the fact that people who are homeless are much more likely to be victims of crime [15]. Research has demonstrated that people who engage in such income generating activities do so because they provide 'cash in hand' on a daily basis needed to meet subsistence needs [19].…”
Section: The Canadian Response To Homelessnessmentioning
confidence: 99%
“…"Moral panics" about squeegeeers and panhandlers began to be played out in the media in cities like Toronto and Montreal, where this highly visible form of poverty became framed as a noticeable manifestation of urban decay [13,14]. Homeless squeegeers and panhandlers were often depicted as dangerous and bad individuals avoiding real work (reminiscent of 19 th century concerns about 'street urchins') and as a threat to downtown businesses, tourism and urban life in general decay [13][14][15].…”
Section: The Emergence Of Homelessness As a Problem In Canadamentioning
confidence: 99%
“…La majorité des recherches sur les jeunes itinérants illustrent qu'ils ont vécu une enfance en proie à la victimisation (abus, négligence et abandon) les poussant à fuir leur milieu et à trouver refuge dans les rues (Baron, 2003a ;Cauce et al, 2000 ;Gaetz, 2004 ;Gaetz et O'Grady, 2002 ;Gilbert, 2004 ;Karabanow et al, 2005 ;Karabanow, 2004 ;Kurtz et al, 1991 ;Mounier et Andujo, 2003 ;Public Health Agency of Canada, 2006). De plus, les mauvaises pratiques d'éducation et les relations parent/enfant difficiles (DiPaolo, 1999 ;Gilbert, 2004 ;Stefanidis et al, 1992 ;Whitbeck et al, 1999 ;Whitbeck et Simons, 1990), l'éclatement, l'instabilité et la recomposition des familles (Bearsley-Smith, 2008 ;Bellot, 2001 ;Caputo, 1997 ;Jones, 1997 ;Laird, 2007) sont des facteurs de risque qui placent ces jeunes dans des positions plus probables d'itinérance, de victimisation et d'engagement dans des activités déviantes (Baron et al, 2007 ;Whitbeck et al, 1999).…”
unclassified
“…De plus, les mauvaises pratiques d'éducation et les relations parent/enfant difficiles (DiPaolo, 1999 ;Gilbert, 2004 ;Stefanidis et al, 1992 ;Whitbeck et al, 1999 ;Whitbeck et Simons, 1990), l'éclatement, l'instabilité et la recomposition des familles (Bearsley-Smith, 2008 ;Bellot, 2001 ;Caputo, 1997 ;Jones, 1997 ;Laird, 2007) sont des facteurs de risque qui placent ces jeunes dans des positions plus probables d'itinérance, de victimisation et d'engagement dans des activités déviantes (Baron et al, 2007 ;Whitbeck et al, 1999). Certains auteurs soulignent que ces facteurs et fissures fournissent un puissant mélange et un « terrain d'entraînement » pour la délinquance (Baron et al, 2007 ;Whitbeck et al, 1997) ainsi que des conditions favorables à la victimisation (Boivin et al, 2005 ;Cauce et al, 2000 ;Gaetz, 2004 ;Hoyt et al, 1999 ;Hwang, 2000 ;Roy et al, 2004).…”
unclassified
See 1 more Smart Citation